2018
DOI: 10.1007/s10597-018-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Blame Among Suicide Survivors: A Qualitative Analysis on Reports of 4-Year Self-Help-Group Meetings

Abstract: This article presents the qualitative analysis of reports obtained through participant observations collected over a three-year period in a series of suicide survivor self-help group meetings. The aim was to analyze how grievers' healing was managed by their own support. The group was composed by 2 men and 8 women and the meetings happened between April 2013 and May 2016 (usually one time per week). Results show how self-blame was continuously present along all the period and how it increased when new particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…The process was structured following six main phases: preparatory organisation, reading and re-reading to recognise key concepts, coding data, interpreting themes, searching for alternative explanations and producing the final report [34,35]. The process proceeded in a 'bottom-up' manner, wherein categories only became clear as the analysis unfolded and as we explored the connections between explicit statements and implicit meanings [30][31][32][33][34][35][36][37][38][39][40]. We performed the analysis with ATLAS.ti, a computer programme that can identify the thematic networks [38,41].…”
Section: The Instruments and The Qualitative Methodsmentioning
confidence: 99%
“…The process was structured following six main phases: preparatory organisation, reading and re-reading to recognise key concepts, coding data, interpreting themes, searching for alternative explanations and producing the final report [34,35]. The process proceeded in a 'bottom-up' manner, wherein categories only became clear as the analysis unfolded and as we explored the connections between explicit statements and implicit meanings [30][31][32][33][34][35][36][37][38][39][40]. We performed the analysis with ATLAS.ti, a computer programme that can identify the thematic networks [38,41].…”
Section: The Instruments and The Qualitative Methodsmentioning
confidence: 99%
“…This study pertains to the field of qualitative research in psychology ( Camic et al, 2003 ), adopting the qualitative-phenomenological approach considered in the literature to be the most reliable for investigating people’s life experiences and their interpretation of meanings ( Denzin, 1995 ; Gill, 2014 ; Pietkiewicz and Smith, 2014 ; Testoni et al, 2018a , b ). The combination of the emic view of the participants and the interpretative etic view of the researchers helps the understanding of cultural issues on health and practicalissues ( Sanjek, 2000 ; Oliffe and Bottorff, 2006 ; Testoni et al, 2018c ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent qualitative studies among suicide-loss survivors have shown that forgiving themselves is one of the toughest struggles in their bereavement process, yet, crucial for their recovery (33)(34)(35). Considering the strong guilt feelings and disproportionate responsibility that often characterize suicide-loss survivors, perhaps adopting some elements of SF could address their feelings and promote adaptive coping with them.…”
Section: Introductionmentioning
confidence: 99%